A New Method for Solving Monotone Generalized Variational Inequalities. (12th October 2010) - Anh, Pham Ngoc; Kim, Jong Kyu
Abstract : We suggest new dual algorithms and iterative methods for solving monotone generalized variational inequalities. Instead of working on the primal space, this method performs a dual step on the dual space by using the dual gap function. Under the suitable conditions, we prove the convergence of the proposed algorithms and estimate their complexity to reach anε -solution. Some preliminary computational results are reported.